2003
DOI: 10.1108/03090560310454037
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the quality of relationships in consumer services: an empirical study

Abstract: Increasingly, firms are recognizing the value of establishing close relationships with their customers as a means of retaining existing customers. Also, firms are realizing that the intangible aspects of a relationship are not easily duplicated by competition, thus providing a sustainable competitive advantage to the firm. In this paper, we provide firms with a scale for measuring the quality of these intangible relationships between service firms and their customers. We then test this scale against the relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
530
2
25

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(575 citation statements)
references
References 110 publications
18
530
2
25
Order By: Relevance
“…For example, studies on the higher order relationship quality concept suggest trust, satisfaction and commitment to be dimensions or antecedents of the construct (Hutchinson et al, 2010;Rauyruen and Miller, 2007;Roberts et al, 2003;Skarmeas and Robson, 2008). In contrast, other researchers suggest that satisfaction is antecedent to trust and commitment (Ha and Muthaly, 2008;Hennig-Thurau et al, 2002;Moliner, 2007aMoliner, , 2007b, while others suggest trust and commitment are antecedent to satisfaction (Farrelly and Quester, 2005;Walter et al, 2000), or only by trust as an antecedent (Anderson and Narus, 1990;Ganesan, 1994;Mohr and Spekman, 1994).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, studies on the higher order relationship quality concept suggest trust, satisfaction and commitment to be dimensions or antecedents of the construct (Hutchinson et al, 2010;Rauyruen and Miller, 2007;Roberts et al, 2003;Skarmeas and Robson, 2008). In contrast, other researchers suggest that satisfaction is antecedent to trust and commitment (Ha and Muthaly, 2008;Hennig-Thurau et al, 2002;Moliner, 2007aMoliner, , 2007b, while others suggest trust and commitment are antecedent to satisfaction (Farrelly and Quester, 2005;Walter et al, 2000), or only by trust as an antecedent (Anderson and Narus, 1990;Ganesan, 1994;Mohr and Spekman, 1994).…”
Section: Introductionmentioning
confidence: 95%
“…A number of researchers have investigated these dimensions as part of a higher order construct, relationship quality, in B2B as well as business to consumer (B2C) situations (Dorsch et al, 1998;Hennig-Thurau and Klee, 1997;Hewett et al, 2002;Roberts et al, 2003;Shamdasani and Balakrishnan, 2000;Svensson et al, 2009;Walter et al, 2003;Wong and Sohal, 2002). In a number of studies, trust and commitment are presented as independent concepts (Hewett et al, 2002;Morgan and Hunt, 1994;Ruyter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Grönroos (2004) found that the nature of the relationship formed between customers and the brands they purchase creates additional value for the customer beyond the value obtained through the purchase of the good or service itself. With a focus on creating strong long-term bonds with customers, relationship marketing not only produces increased customer retention and loyalty, it also provides barriers to entry for competitors since they are unable to easily replicate the relationship between the customer and service provider (Roberts, Varki & Brodie, 2003). The objective of relationship marketing activities is therefore to form long lasting relationships with consumers which increase the potential for positive referral, repurchase and loyalty (Sheth and Parvatiyar 1995;Palmatier, Dant, Grewal & Evans, 2006;Hennig-Thurau et al 2002;Reichheld 2003;Mattila 2006).…”
Section: Developing a Relationship Marketing Orientation In Higher Edmentioning
confidence: 99%
“…In other words, relationship quality refers to customers' perception of relationship outcomes in terms of fulfilling their expectations and desires (Wong & Sohal, 2002). Roberts et al (2003) defined relationship quality as "a measure of the extent to which consumers want to maintain relationships with their service providers" (p. 191). Therefore, it can be suggested from the above definitions that relationship quality is concerned with overall nature of the relationship between a brand and its customers taking into account the extent of fulfilling the needs and expectations in determining relationship success (Hennig-Thurau, Langer, & Hansen, 2002).…”
Section: Relationship Qualitymentioning
confidence: 99%
“…Successful relationship marketing also grants brands with sustainable competitive advantages (Anderson and Narus, 1990;Roberts, Varki and Brodie, 2003). According to Ford (1980), high quality of relationships between organizations and their customers connect both parties to each other in a manner that they are capable to obtain advantages beyond the mere exchange of products.…”
mentioning
confidence: 99%